The effect of interface atomic structure on the deformation mechanisms of Ti2AlN/TiAl composite under nanoindentation using MD simulations. (31st January 2019) - Liu, Pei; Han, Xiuli; Sun, Dongli; Wang, Qing
Abstract: In this study, we conduct molecular dynamics simulations to investigate the effect of interface atomic structure on the deformation mechanisms of Ti2 AlN/TiAl composite under nanoindentation. It is found that the interface atomic structure has a remarkable effect on the deformation behavior of Ti2 AlN/TiAl composite due to significantly different interface-dislocation interactive mechanisms. For the Ti2 AlN(0 0 0 1)/TiAl(1 1 1) coherent interface system, although plenty of dislocations nucleate and propagate through the TiAl layer during the indentation process, there are no dislocations transmitting across the coherent interface. The formation of stair-rod dislocation and dislocation tangle is the major mechanism for blocking the slip motion of dislocations by the coherent interface. Thus, the Ti2 AlN(0 0 0 1)/TiAl(1 1 1) coherent interface is beneficial for the strengthening effect of Ti2 AlN/TiAl composite. For the Ti2 AlN(1 0 3)/TiAl(1 1 1) incoherent interface system, the incoherent interface has some ability to annihilate the dislocations nucleated from the TiAl during the indentation process, but it cannot simultaneously annihilate plenty of dislocations. These dislocations accumulate in the incoherent interface and cause the stress concentration, providing the driving force for dislocation nucleation in Ti2 AlN from the poor matching regions in the Al atomic arrays at the incoherent interface. Therefore, the incoherent interface can provide the access of dislocation transmission from TiAl to Ti2 AlN, which benefits the ductility of Ti2 AlN/TiAl composite.